Antique grey tile fired by oxidizing flame and preparation method of antique grey tile

Through the oxidation flame firing process and specific raw material ratio, the existing antique green tiles have been solved, and the effects of shortening the firing cycle, reducing costs and improving performance are achieved.

CN119797887APending Publication Date: 2025-04-11GUANGXI NANSHAN PORCELAIN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411849432.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing antique green tiles have a long burning time, high cost, and complex production processes, which limit industrial development.

Method used

The antique green tiles are prepared by using the oxidation flame firing process, using raw materials such as limestone, wood crypt, Liuliang mud, black mud and manganese ore, through ball milling, pressing, drying and high-temperature oxidation flame firing.

Benefits of technology

The firing cycle has been shortened to about 5 hours, the raw material cost has been reduced, the product color is uniform and the various physical and chemical properties have met the national industry requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190169570000081
    Figure BDA0005190169570000081
Patent Text Reader

Abstract

The invention discloses an antique grey tile fired by oxidizing flame and a preparation method of the antique grey tile, and relates to the technical field of building materials. The oxidizing flame fired antique grey tile comprises the following raw materials in percentage by weight: 2-7% of limestone, 15-22% of wood cellar soil, 20-30% of Liuliang mud, 30-42% of black mud and 12-20% of manganese ore. The preparation process comprises the steps of raw material ball milling, mud refining, tile extruding, drying, oxidizing flame high-temperature sintering and delivery, wherein the oxidizing flame high-temperature sintering process comprises the following steps: in a low-temperature stage, preserving heat at 280-450 DEG C for 0.8-1.0 h; in the medium-temperature low-oxidation stage, the temperature is kept at 750-850 DEG C for 1.0-1.5 h; in the high-temperature strong oxidation stage, the temperature is kept at 950-1080 DEG C for 1.5-1.8 h; in the high-temperature heat preservation stage, heat preservation is conducted for 0.8-1.0 h at the temperature of 1150-1180 In the quenching stage, heat preservation is conducted for 0.5-0.7 h at the temperature of 1180-800 DEG C; in the product slow cooling stage, heat preservation is conducted for 1.0-1.2 h at the temperature of 800-580 DEG C; and naturally cooling to obtain the product. The archaized grey tile is short in firing time, uniform in color and luster and free of color difference, and various physical and chemical properties meet the national industry requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an oxidizing flame fired antique blue tile and a preparation method thereof. Background Art

[0002] Traditional antique blue tiles are mainly made of clay, and the finished product is blue-gray, giving people a simple, calm, simple and peaceful aesthetic feeling. It is one of the products that designers have strongly recommended in recent years. At present, the antique blue tiles on the market are all fired in the traditional reducing flame atmosphere, and finally the antique blue tone is achieved through the water-cooled sealed kiln change process. This manufacturing process is quite complicated. The main purpose of firing in the reducing atmosphere is to reduce the red high-priced iron oxide in the mud into blue-green ferrous oxide. This traditional firing process consumes a lot of fuel costs and has a long firing cycle, which can last for more than 20 days or even a month, and the shortest is ten days or eight days. The traditional reduction firing process has seriously restricted the development of the current antique blue tile industry.

[0003] In the prior art, construction waste tailings, curing agent, cement, colorant and water are also used as raw materials to prepare unfired antique blue bricks (CN 112408905 B is an unfired antique blue brick based on construction waste tailings) or unfired antique blue tiles are made using machine-made sand tailings (CN 118666544 A is an unfired antique blue tile made using machine-made sand tailings), but a lot of auxiliary materials need to be added during the production, the cost is high, and its stability and service life need to be further improved.

[0004] In summary, the object of the present invention is to provide an oxidizing flame fired antique blue tile and a preparation method thereof. Summary of the invention

[0005] In view of the above shortcomings, the present invention provides an oxidizing flame fired antique blue tile and a preparation method thereof, which solves the problem of long firing time and high cost of existing antique blue tile products. The present invention only needs less raw materials and shorter firing time to prepare products with uniform color, no color difference, and various physical and chemical properties that meet national industry requirements. The specific technical scheme is as follows:

[0006] The invention discloses an antique blue tile fired by oxidation flame, comprising the following raw materials in percentage by weight: 2-7% limestone, 15-22% wood cellar soil, 20-30% Liuliang mud, 30-42% black mud and 12-20% manganese ore.

[0007] Preferably, the limestone comprises the following chemical components by mass percentage: 1-3% silicon oxide, 0.1-0.2% aluminum oxide, 0.05-0.09% iron oxide, 0.008-0.015% titanium dioxide, 53-58% calcium oxide, 0.01-0.05% magnesium oxide, 0.1-0.2% potassium oxide, 0.05-0.15% sodium oxide and 35-43% loss on ignition.

[0008] Preferably, the wood pit soil comprises the following chemical components by mass percentage: 60-66% silicon oxide, 5-8% aluminum oxide, 18-24% iron oxide, 1-2.5% titanium dioxide, 0.1-0.2% calcium oxide, 0.01-0.03% magnesium oxide, 1-2% potassium oxide, 0.3-5% sodium oxide and 2-4% loss on ignition.

[0009] Preferably, the Liuliang mud comprises the following chemical components by mass percentage: 62-66% silicon oxide, 10-15% aluminum oxide, 14-17% iron oxide, 0.5-1.5% titanium dioxide, 0.1-0.25% calcium oxide, 0.2-0.5% magnesium oxide, 0.5-1.5% potassium oxide, 0.3-0.6% sodium oxide and 2-6% loss on ignition.

[0010] Preferably, the black mud comprises the following chemical components by mass percentage: 58-63% silicon oxide, 22-26% aluminum oxide, 0.5-1.0% iron oxide, 0.1-0.3% titanium dioxide, 0.1-0.25% calcium oxide, 0.05-0.09% magnesium oxide, 0.1-0.3% potassium oxide, 0.4-0.7% sodium oxide and 10-13% loss on ignition.

[0011] Preferably, the manganese ore comprises the following chemical components by mass percentage: 55-60% silicon oxide, 7-10% aluminum oxide, 2-4% iron oxide, 10-13% manganese dioxide, 0.5-0.8% calcium oxide, 0.7-1.0% magnesium oxide, 1-1.5% potassium oxide, 0.5-0.8% sodium oxide and 10-14% loss on ignition.

[0012] Preferably, the raw materials include the following chemical components by mass percentage: 58-60% silicon oxide, 13.5-15% aluminum oxide, 8-9.5% iron oxide, 2.5-3.1% manganese dioxide, 2.8-3.6% calcium oxide, 0.2-0.3% magnesium oxide, 0.4-0.6% titanium dioxide, 0.5-0.8% potassium oxide, 0.2-0.8% sodium oxide and 8-10% loss on ignition.

[0013] The present invention also provides a method for preparing the above-mentioned antique blue tiles fired by oxidizing flame, comprising the following steps:

[0014] (1) Take the raw materials according to the proportion and ball mill them to obtain mud.

[0015] (2) The mud is squeezed into a mud cake, the moisture content of which is controlled at 17.5-19%, and the mud is kneaded by a mud refiner. A forming sleeve is directly installed at the mud outlet of the mud refiner to extrude tiles, thereby obtaining green tiles.

[0016] (3) Drying: The green tile is placed in a drying room and dried at 50-65°C to a moisture content of 1-2%. Controlling the moisture content at 1-2% is conducive to rapid firing. If the moisture content of the green tile is higher than 2%, the green tile will explode during rapid firing, which is not conducive to achieving rapid firing.

[0017] (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the green tile preheating stage, the kiln temperature is 280-450℃, and the insulation time is 0.8-1.0h; the medium temperature low oxidation stage, the kiln temperature is 750-850℃, and the insulation time is 1.0-1.5h; the high temperature strong oxidation stage, the kiln temperature is 950-1080℃, and the insulation time is 1.5-1.8h; the high temperature insulation stage, the kiln temperature is 1150-1180℃, and the insulation time is 0.8-1.0h; the rapid cooling stage, the kiln temperature is 1180-800℃, and the insulation time is 0.5-0.7h; the product slow cooling stage, the kiln temperature is 800-580℃, and the insulation time is 1.0-1.2h; natural cooling, the firing process is completed.

[0018] (5) Leave the factory.

[0019] Preferably, in step (1), the ball milling is to first wet-mill the Liuliang mud and manganese ore together for 20-24 hours, and control the fineness to be 0.02-0.05% of the residue after passing through a 250-mesh sieve to obtain a mixture; and add the limestone, wood cellar soil and black mud to the mixture and wet-mill them together for 1-2 hours, and detect the residue after passing through a 160-mesh sieve to obtain 3.5-4.5%.

[0020] Preferably, in step (3), the drying temperature is 55-60°C.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The antique blue tile of the present invention is made of local wood pit soil with high iron content, Liuliang mud with high iron ore content, and Luchuan black mud with good bonding properties as main materials, and is made by high-temperature rapid firing in a kiln with strong oxidation atmosphere, and its firing cycle is about 5 hours, the firing time is short, and the raw material cost is low. The antique blue tile product made by the method of the present invention has uniform color and no color difference, and all physical and chemical performance tests meet national industry requirements. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0024] Example 1

[0025] The invention discloses an antique blue tile fired by oxidizing flame, comprising the following raw materials in percentage by weight: 2% limestone, 15% wood cellar soil, 30% Liuliang mud, 41% black mud and 12% manganese ore.

[0026] The limestone is Guangxi Yulin limestone, which includes the following chemical components by mass percentage: 3% silicon oxide, 0.2% aluminum oxide, 0.09% iron oxide, 0.01% titanium dioxide, 54% calcium oxide, 0.01% magnesium oxide, 0.1% potassium oxide, 0.05% sodium oxide and 42.54% loss on ignition.

[0027] The Mujiao soil is from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 64.59% silicon oxide, 8% aluminum oxide, 23% iron oxide, 1% titanium dioxide, 0.1% calcium oxide, 0.01% magnesium oxide, 1% potassium oxide, 0.3% sodium oxide and 2% loss on ignition.

[0028] The Liuliang mud is Liuliang mud from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 64.4% silicon oxide, 15% aluminum oxide, 17% iron oxide, 0.5% titanium dioxide, 0.1% calcium oxide, 0.2% magnesium oxide, 0.5% potassium oxide, 0.3% sodium oxide and 2% loss on ignition.

[0029] The black mud is from Luchuan County, Guangxi, and includes the following chemical components by mass percentage: 62.25% silicon oxide, 26% aluminum oxide, 1.0% iron oxide, 0.1% titanium dioxide, 0.1% calcium oxide, 0.05% magnesium oxide, 0.1% potassium oxide, 0.4% sodium oxide and 10% loss on ignition.

[0030] The manganese ore is from Pingnan County, Guangxi, and includes the following chemical components by mass percentage: 60% silicon oxide, 10% aluminum oxide, 4% iron oxide, 11.3% manganese dioxide, 0.5% calcium oxide, 0.7% magnesium oxide, 1% potassium oxide, 0.5% sodium oxide and 12% loss on ignition.

[0031] The raw materials include the following chemical components by mass percentage: 60% silicon oxide, 15% aluminum oxide, 9.5% iron oxide, 3.1% manganese dioxide, 3.1% calcium oxide, 0.2% magnesium oxide, 0.4% titanium dioxide, 0.5% potassium oxide, 0.2% sodium oxide and 8% loss on ignition.

[0032] The method for preparing antique blue tiles fired by oxidizing flame comprises the following steps:

[0033] (1) ball milling the raw materials according to the proportion: first, wet ball milling the Liuliang mud and manganese ore for 20 hours, and controlling the fineness to 0.02% of the residue after passing through a 250-mesh sieve to obtain a mixture; adding the limestone, wood cellar soil and black mud to the mixture, and wet ball milling for 1 hour, and detecting the residue after passing through a 160-mesh sieve to obtain a slurry.

[0034] (2) The mud is squeezed into a mud cake, the moisture content of which is controlled at 17.5%, and the mud is kneaded by a mud refiner, and a forming sleeve is directly installed at the mud outlet of the mud refiner to squeeze tiles to obtain tile blanks;

[0035] (3) Drying: The drying temperature in the drying room is controlled at 50 degrees, and the moisture content of the tile after drying is controlled at 1%.

[0036] (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the preheating stage of the green tiles, the kiln temperature is 280℃, and the insulation time is 1.0h; the medium temperature low oxidation stage, the kiln temperature is 750℃, and the insulation time is 1.5h; the high temperature strong oxidation stage, the kiln temperature is 950℃, and the insulation time is 1.8h; the high temperature insulation stage, the kiln temperature is 1150℃, and the insulation time is 1.0h; the rapid cooling stage is the key stage for product color control, the kiln temperature is 1180℃, and the insulation time is 0.5h; the product slow cooling stage, the kiln temperature is 800℃, and the insulation time is 1.2h; natural cooling can complete the firing process.

[0037] (5) Leave the factory.

[0038] Example 2

[0039] The invention discloses an antique blue tile fired by oxidizing flame, comprising the following raw materials in percentage by weight: 7% limestone, 22% wood cellar soil, 20% Liuliang mud, 31% black mud and 20% manganese ore.

[0040] The limestone is Guangxi Yulin limestone, which includes the following chemical components by mass percentage: 1.955% silicon oxide, 0.15% aluminum oxide, 0.08% iron oxide, 0.015% titanium dioxide, 58% calcium oxide, 0.05% magnesium oxide, 0.2% potassium oxide, 0.15% sodium oxide and 39.4% loss on ignition.

[0041] The wood cave soil is from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 63% silicon oxide, 6% aluminum oxide, 19% iron oxide, 2.5% titanium dioxide, 0.2% calcium oxide, 0.03% magnesium oxide, 2% potassium oxide, 5% sodium oxide and 2.27% loss on ignition.

[0042] The Liuliang mud is Liuliang mud from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 64% silicon oxide, 13% aluminum oxide, 16% iron oxide, 1.5% titanium dioxide, 0.25% calcium oxide, 0.5% magnesium oxide, 1.5% potassium oxide, 0.6% sodium oxide and 2.65% loss on ignition.

[0043] The black mud is from Luchuan County, Guangxi, and includes the following chemical components by mass percentage: 61% silicon oxide, 25% aluminum oxide, 0.8% iron oxide, 0.3% titanium dioxide, 0.25% calcium oxide, 0.09% magnesium oxide, 0.3% potassium oxide, 0.7% sodium oxide and 11.56% loss on ignition.

[0044] The manganese ore is from Pingnan County, Guangxi, and includes the following chemical components by mass percentage: 58% silicon oxide, 9% aluminum oxide, 3% iron oxide, 13% manganese dioxide, 0.8% calcium oxide, 1.0% magnesium oxide, 1.5% potassium oxide, 0.8% sodium oxide and 12.9% loss on ignition.

[0045] The raw materials include the following chemical components by mass percentage: 58.4% silicon oxide, 14% aluminum oxide, 8.5% iron oxide, 3% manganese dioxide, 3.6% calcium oxide, 0.3% magnesium oxide, 0.6% titanium dioxide, 0.8% potassium oxide, 0.8% sodium oxide and 10% loss on ignition.

[0046] The method for preparing antique blue tiles fired by oxidizing flame comprises the following steps:

[0047] (1) ball milling the raw materials according to the proportion: first, wet ball milling the Liuliang mud and manganese ore for 22 hours, and controlling the fineness to 0.05% of the residue after passing through a 250-mesh sieve to obtain a mixture; adding the limestone, wood cellar soil and black mud to the mixture, and wet ball milling for 2 hours, and detecting the residue after passing through a 160-mesh sieve to obtain a slurry.

[0048] (2) The mud is squeezed into a mud cake, and the moisture content is controlled at 19%. The mud is kneaded by a mud refiner and a forming sleeve is directly installed at the mud outlet of the mud refiner to squeeze tiles.

[0049] (3) Drying: The drying temperature in the drying room is controlled at 65 degrees, and the moisture content of the tile after drying is controlled at 2%.

[0050] (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the preheating stage of the green tiles, the kiln temperature is 450℃, and the insulation time is 0.8h; the medium temperature low oxidation stage, the kiln temperature is 850℃, and the insulation time is 1.0h; the high temperature strong oxidation stage, the kiln temperature is 1080℃, and the insulation time is 1.5h; the high temperature insulation stage, the kiln temperature is 1180℃, and the insulation time is 0.8h; the rapid cooling stage is the key stage for product color control, the kiln temperature is 800℃, and the insulation time is 0.7h; the product slow cooling stage, the kiln temperature is 580℃, and the insulation time is 1.2h; natural cooling can complete the firing process.

[0051] (5) Leave the factory.

[0052] Example 3

[0053] The invention discloses an antique blue tile fired by oxidizing flame, comprising the following raw materials in percentage by weight: 5% limestone, 18% wood cellar soil, 26% Liuliang mud, 35% black mud and 16% manganese ore.

[0054] The limestone is Guangxi Yulin limestone, which includes the following chemical components by mass percentage: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss of 41.28%.

[0055] The wood cave soil is from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 64.86% silicon oxide, 7.52% aluminum oxide, 21.12% iron oxide, 1.56% titanium dioxide, 0.11% calcium oxide, 0.02% magnesium oxide, 1.21% potassium oxide, 0.45% sodium oxide, and 3.15% loss on ignition.

[0056] The Liuliang mud is Liuliang mud from Lingshan Town, Rong County, Guangxi, and includes the following chemical components by mass percentage: 64.96% silicon oxide, 13.01% aluminum oxide, 15.03% iron oxide, 0.91% titanium dioxide, 0.15% calcium oxide, 0.32% magnesium oxide, 1.02% potassium oxide, 0.47% sodium oxide, and 4.13% loss on ignition.

[0057] The black mud is from Luchuan County, Guangxi, and includes the following chemical components by mass percentage: 60.97% silicon oxide, 25.61% aluminum oxide, 0.89% iron oxide, 0.25% titanium dioxide, 0.16% calcium oxide, 0.07% magnesium oxide, 0.25% potassium oxide, 0.65% sodium oxide, and 11.15% loss on ignition.

[0058] The manganese ore is from Pingnan County, Guangxi, and includes the following chemical components by mass percentage: 59.38% silicon oxide, 8.91% aluminum oxide, 3.48% iron oxide, 12.35% manganese dioxide, 0.76% calcium oxide, 0.97% magnesium oxide, 1.25% potassium oxide, 0.73% sodium oxide, and 12.17% loss on ignition.

[0059] The raw materials include the following chemical components by mass percentage: 59.29% silicon oxide, 15% aluminum oxide, 8.77% iron oxide, 2.5% manganese dioxide, 3.01% calcium oxide, 0.25% magnesium oxide, 0.51% titanium dioxide, 0.65% potassium oxide, 0.54% sodium oxide, and 9.48% loss on ignition.

[0060] The method for preparing antique blue tiles fired by oxidizing flame comprises the following steps:

[0061] (1) ball milling the raw materials according to the proportion: first, wet ball milling the Liuliang mud and manganese ore for 24 hours, and controlling the fineness to be 0.04% on a 250-mesh sieve, to obtain a mixture; adding the limestone, wood cellar soil and black mud to the mixture, and wet ball milling for 2 hours, and detecting the sieve residue through a 160-mesh sieve to be 4%, to obtain mud.

[0062] (2) The mud is squeezed into a mud cake, the moisture content of which is controlled at 18%, and the mud is kneaded by a mud refiner, and a forming sleeve is directly installed at the mud outlet of the mud refiner to squeeze tiles to obtain tile blanks;

[0063] (3) The drying temperature in the drying room is controlled at 58 degrees, and the moisture content of the tile after drying is controlled at 1.5%.

[0064] (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the preheating stage of the green tiles, the kiln temperature is 400°C, and the insulation time is 0.9h; the medium temperature low oxidation stage, the kiln temperature is 800°C, and the insulation time is 1.3h; the high temperature strong oxidation stage, the kiln temperature is 1000°C, and the insulation time is 1.7h; the high temperature insulation stage, the kiln temperature is 1170°C, and the insulation time is 0.9h; the rapid cooling stage is the key stage for product color control, the kiln temperature is 900°C, and the insulation time is 0.6h; the product slow cooling stage, the kiln temperature is 600°C, and the insulation time is 1.1h; natural cooling can complete the firing process.

[0065] (5) Leave the factory.

[0066] Comparative Example 1

[0067] The antique blue tile of this comparative example comprises the following raw materials in weight percentage: 2% limestone, 15% wood pit soil, 30% clay, 41% black mud and 12% manganese ore. That is, it does not contain Liuliang mud, and an equal amount of clay is used to replace Liuliang mud. The other preparation methods are the same as those in Example 1.

[0068] Comparative Example 2

[0069] The antique blue tile of this comparative example comprises the following raw materials in weight percentage: 2% limestone, 15% wood pit soil, 30% Liuliang mud, 41% black mud and 12% clay. That is, it does not contain manganese ore, and uses an equal amount of clay to replace manganese ore. The other preparation methods are the same as those of Example 1.

[0070] Comparative Example 3

[0071] The raw materials and proportions of the antique blue tiles in this comparative example are the same as those in Example 1.

[0072] The preparation method is:

[0073] (1) ball milling the raw materials according to the proportion: first, wet ball milling the Liuliang mud and manganese ore for 20 hours, and controlling the fineness to 0.02% of the residue after passing through a 250-mesh sieve to obtain a mixture; adding the limestone, wood cellar soil and black mud to the mixture, and wet ball milling for 1 hour, and detecting the residue after passing through a 160-mesh sieve to obtain a slurry.

[0074] (2) The mud is squeezed into a mud cake, the moisture content of which is controlled at 17.5%, and the mud is kneaded by a mud refiner, and a forming sleeve is directly installed at the mud outlet of the mud refiner to squeeze tiles to obtain tile blanks;

[0075] (3) Drying: The drying temperature in the drying room is controlled at 50 degrees, and the moisture content of the tile after drying is controlled at 1%.

[0076] (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the green tile preheating stage, the kiln temperature is 280℃, and the insulation time is 1.0h; the medium temperature low oxidation stage, the kiln temperature is 750℃, and the insulation time is 1.5h; the high temperature strong oxidation stage, the kiln temperature is 950℃, and the insulation time is 1.8h; the high temperature insulation stage, the kiln temperature is 1150℃, and the insulation time is 1.0h; the product slow cooling stage, the kiln temperature is 800℃, and the insulation time is 1.2h; natural cooling can complete the firing process. That is, there is no rapid cooling stage, and the product is directly slowly cooled.

[0077] According to the method of industry standard WW / T 0050-2014 "Basic Materials for the Maintenance of Cultural Relics Buildings: Green Tiles", the appearance, bending resistance, freeze-thaw resistance, anti-penetration performance, water absorption rate and frost of the antique green tiles prepared in each embodiment and comparative example were tested. Among them, if the bending failure load of the antique green tiles is not less than 850N, then its bending resistance meets the requirements; if there is no increase in defects such as peeling, corner loss, edge loss, alkali brittleness and cracks after 15 freeze-thaw cycles, then the freeze-thaw resistance meets the requirements; if there is no dripping of water on the back of the tile after 3 hours, then the anti-penetration performance meets the requirements; the water absorption rate is less than 17.0%, which meets the requirements; the frost degree is no frost, which meets the requirements; the results are shown in Table 1:

[0078] Table 1 Comparison of product performance in each group

[0079]

[0080] Note: No blooming: no visible salt precipitation on the surface of the sample; Slight blooming: a thin and obvious frost film appears on the surface of the sample, but the surface of the sample is still clear; Moderate blooming: obvious frost layer appears on part of the surface or corners of the sample; Severe blooming: flaking, scaling and peeling appear on the surface of the sample.

[0081] The table shows that Liuliang mud and manganese ore have certain effects on product appearance, bending resistance, freeze-thaw resistance, penetration resistance, water absorption and frosting. At the same time, the absence of a rapid cooling stage during preparation will also affect these properties. The antique blue tile product obtained by the preparation method of the present invention has uniform color without color difference, and all physical and chemical performance tests meet national industry requirements.

[0082] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. An oxidizing flame fired antique blue tile, characterized in that: The invention comprises the following raw materials in percentage by weight: 2-7% of limestone, 15-22% of wood pit soil, 20-30% of Liuliang mud, 30-42% of black mud and 12-20% of manganese ore.

2. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The limestone comprises the following chemical components by mass percentage: 1-3% silicon oxide, 0.1-0.2% aluminum oxide, 0.05-0.09% iron oxide, 0.008-0.015% titanium dioxide, 53-58% calcium oxide, 0.01-0.05% magnesium oxide, 0.1-0.2% potassium oxide, 0.05-0.15% sodium oxide and ignition loss 35-43%.

3. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The wood pit soil comprises the following chemical components by mass percentage: 60-66% silicon oxide, 5-8% aluminum oxide, 18-24% iron oxide, 1-2.5% titanium dioxide, 0.1-0.2% calcium oxide, 0.01-0.03% magnesium oxide, 1-2% potassium oxide, 0.3-5% sodium oxide and 2-4% loss on ignition.

4. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The Liuliang mud includes the following chemical components by mass percentage: 62-66% silicon oxide, 10-15% aluminum oxide, 14-17% iron oxide, 0.5-1.5% titanium dioxide, 0.1-0.25% calcium oxide, 0.2-0.5% magnesium oxide, 0.5-1.5% potassium oxide, 0.3-0.6% sodium oxide and 2-6% loss on ignition.

5. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The black mud comprises the following chemical components by mass percentage: 58-63% silicon oxide, 22-26% aluminum oxide, 0.5-1.0% iron oxide, 0.1-0.3% titanium dioxide, 0.1-0.25% calcium oxide, 0.05-0.09% magnesium oxide, 0.1-0.3% potassium oxide, 0.4-0.7% sodium oxide and 10-13% loss on ignition.

6. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The manganese ore comprises the following chemical components by mass percentage: 55-60% silicon oxide, 7-10% aluminum oxide, 2-4% iron oxide, 10-13% manganese dioxide, 0.5-0.8% calcium oxide, 0.7-1.0% magnesium oxide, 1-1.5% potassium oxide, 0.5-0.8% sodium oxide and 10-14% loss on ignition.

7. The oxidizing flame fired antique blue tile according to claim 1, characterized in that: The raw materials include the following chemical components by mass percentage: 58-60% silicon oxide, 13.5-15% aluminum oxide, 8-9.5% iron oxide, 2.5-3.1% manganese dioxide, 2.8-3.6% calcium oxide, 0.2-0.3% magnesium oxide, 0.4-0.6% titanium dioxide, 0.5-0.8% potassium oxide, 0.2-0.8% sodium oxide and 8-10% loss on ignition.

8. A method for preparing antique blue tiles fired by oxidizing flame according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) ball-milling the raw materials according to the proportions to obtain slurry; (2) squeezing the mud into a mud cake, controlling the moisture content at 17.5-19%, kneading the mud in a mud refiner, squeezing tiles, and obtaining tile blanks; (3) drying: drying the green tile at 50-65° C. until the moisture content is 1-2%; (4) Oxidation flame high temperature firing: The dried green tiles are subjected to oxidation flame high temperature firing, wherein the low temperature stage is the green tile preheating stage, the kiln temperature is 280-450℃, and the insulation time is 0.8-1.0h; the medium temperature low oxidation stage, the kiln temperature is 750-850℃, and the insulation time is 1.0-1.5h; the high temperature strong oxidation stage, the kiln temperature is 950-1080℃, and the insulation time is 1.5-1.8h; In the high temperature insulation stage, the kiln temperature is 1150-1180℃, and the insulation time is 0.8-1.0h; in the rapid cooling stage, the kiln temperature is 1180-800℃, and the insulation time is 0.5-0.7h; in the product slow cooling stage, the kiln temperature is 800-580℃, and the insulation time is 1.0-1.2h; natural cooling can complete the firing process; (5) Leave the factory.

9. The method for preparing antique blue tiles by oxidizing flame firing according to claim 8, characterized in that: In step (1), the ball milling is to first wet-mill the Liuliang mud and manganese ore together for 20-24 hours, and control the fineness to be 0.02-0.05% of the residue after passing through a 250-mesh sieve to obtain a mixture; and add the limestone, wood cellar soil and black mud to the mixture and wet-mill for 1-2 hours, and detect the residue after passing through a 160-mesh sieve to obtain 3.5-4.5%.

10. The method for preparing antique blue tiles fired by oxidizing flame according to claim 8, characterized in that: In step (3), the drying temperature is 55-65 degrees.

Citation Information

Patent Citations

  • Non-fired antique-style bricks based on construction waste tailings, their preparation methods and applications

    CN112408905B

  • Unfired archaized grey tile manufactured by utilizing machine-made sand tailing mud and manufacturing method of unfired archaized grey tile

    CN118666544A